BASICS: to make quality cassava seed available, it has to be profitable - Lawrence Kent - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2017)
BASICS project works towards quality cassava seed availability, Lawrence Kent said for this to happen, it has to be profitable.